Comparative Evaluation of Mammography and Ultrasound in Detecting Breast Masses in Women Under 40 Years - Reena Kumari Sunil, Aisha Asim, Farah Saleem, Aisha Taj, Mahwash Mansoor, Sheema Memon, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Breast cancer is increasingly being diagnosed in younger women, yet diagnostic imaging in this age group remains challenging due to higher breast density and aggressive tumor biology. Mammography is limited in sensitivity among women under 40 years, whereas ultrasound provides a radiation-free, real-time modality that may offer improved detection. Objective: To compare the diagnostic performance of mammography and ultrasound in the detection of breast masses among women younger than 40 years in Pakistan. Methods: A prospective diagnostic accuracy study was conducted at Ziauddin Medical University Hospital, Karachi, and Khyber Teaching Hospital, Peshawar, between January 2022 and March 2023. Ninety women aged 18–39 years with clinically suspected breast masses underwent same-day mammography and targeted breast ultrasound. Images were interpreted independently using BI-RADS criteria. Histopathology from biopsy or 12-month imaging follow-up served as the reference standard. Sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and overall accuracy were calculated for both modalities, and subgroup analyses were performed by age group and breast density. Results: The mean age of participants was 31.4 ± 5.2 years, with 64.4% in the 30–39 year age group. The majority presented with palpable lumps (78.9%). Histopathology confirmed malignancy in 27 cases (30%) and benign lesions in 63 (70%). Ultrasound demonstrated a sensitivity of 92.6%, specificity of 90.5%, PPV of 80.6%, NPV of 96.6%, and overall accuracy of 91.1%. Mammography achieved a sensitivity of 74.1%, specificity of 85.7%, PPV of 69.0%, NPV of 88.5%, and accuracy of 82.2%. Ultrasound outperformed mammography in invasive carcinomas, while mammography remained superior in detecting microcalcification-dominant DCIS. Subgroup analyses showed ultrasound was particularly advantageous in younger women (18–29 years) and those with dense breasts. Conclusion: Ultrasound is more sensitive and diagnostically accurate than mammography for breast mass detection in women under 40 years, especially in dense breast tissue. Mammography, while less sensitive overall, retains complementary value for identifying microcalcification-based lesions. Ultrasound should be considered the primary imaging modality in this age group, with selective mammography reserved for equivocal cases or suspected DCIS. Keywords: Breast ultrasound, mammography, dense breast, BI-RADS, young women, diagnostic accuracy